The Analysis of Moral Value In The Cockroach Opera Script By N Riantiarno - Nuris Imam Sholihin (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2022)
Drama script is anelement that forms theatrical performances. A good quality script certainly has a moral value to be conveyed by the author to the reader or the appreciator of the show when it is staged in a performance. Talking about art nowadays, it can be seen in the expression of human creativity. Art is very difficult to both explain and judge since each artist selects his or her rules and parameters guiding them into their works. It can be inferred that art has three points: a process and product of choosing a medium, a set of rules to use a medium, and a set of values determining what is appropriate to be conveyed by expression through that medium, in order to deliver either a belief, idea, sensation or feeling effectively. Moral value is a message in a story or other works that the author wants to convey to the reader. The message to be conveyed is usually in the form of good values that can be used as an example for the readers. In this study, an analysis of the cockroach opera by N. Riantiarno will be conducted based on the study of moral value.